Mechanismus jednoválcového zážehového motoru s prodlouženou expanzí - Tokař, Stanislav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Tato práce se zaměřuje na návrh klikového mechanismu motoru s prodlouženou expanzí. Hlavní pozornost je věnována na vyšetření průběhů kinematických veličin a setrvačných sil v mechanismu. Dále je v této práci provedena analýza napjatosti ojnice a porovnána s ojnicí klasického motoru. V poslední části je zhodnocení předností a nedostatků navrženého řešení mechanismu.

This thesis concentrates on the design of crank-type mechanism of engine with elongated expansion. The main attention is paid to examination of the progress of kinematic quantities and inertial forces in mechanism. Further on in the thesis, the analysis of piston-rod stress is carried out and is compared to the piston-rod of standard engine. In the last part of the thesis, there is an evaluation of advantages and disadvantages of the proposed mechanism solution.
Mechanism of a one-cylinder spark ignition engine with elongated expansion
Keywords: prodloužená expanze; průběh kinematických veličin; ojnice; táhlo; analýza napjatosti; 3-D model; Elongated expansion; progress of kinematic quantities; piston-rod; connecting rod; analysis of stress; 3-D model